Assessment of MRI Safety Practices in Saudi Arabia - Alghamdi,Sami A (Risk Management and Healthcare Policy, 2023)
Sami A Alghamdi Radiological Sciences Department, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Sami A Alghamdi, Email salghamdi1@ksu.edu.saAim: The aim of this study is to investigate the safety practices used by MRI departments in Saudi Arabia.Methods: A cross-sectional study across 113 private and public hospitals was conducted in Saudi Arabia. A survey questionnaire was designed and sent to 113 MRI units. The questionnaire consisted of 43 items under 14 sections for the assessment of MRI safety practices. These 14 sections are related to (i) MRI and its safety, (ii) MRI usage and its safety, and (iii) safety of the MRI technologists and reporting of adverse effects during the usage. The American College of Radiology (ACR) guidance document on MRI safety practices was used as a template for this survey. Data were analyzed using IBM SPSS Statistical software for Windows version 26.0 (IBM Corp., Armonk, NY, USA).Results: Of the 43 items assessed, only 3 items’ binary responses (Yes & No) did not differ much. A greater proportion of positive responses for 40 items (93%) regarding MRI safety practices. More than 50% of the participants claimed that their departments lacked a Magnetic Resonance Safety Officer (MRSO). Regarding regular safety training programs, less than 50% received training in MRI safety. Handheld metal detectors were found in only 39% of the MRI units.Conclusion: The majority of MRI units in Saudi Arabia have demonstrated compliance with majority of ACR MRI safety recommendations; nonetheless, there are two main items for which the guidelines may not be attained: MRSO and regular MRI safety training programs. By taking into account the limitations of this study, it is strongly recommended to assign MRSO and implement annual MRI safety training to improve MRI safety practices for both patients and healthcare workers.Keywords: magnetic resonance imaging, MRI, safety, Saudi Arabia, 2020 American College of Radiology guidelines, ACR